2017
DOI: 10.1007/s00277-017-2991-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of multiple myeloma in Germany: analysis of a nationwide multi-institutional survey

Abstract: A nationwide, multi-institutional survey was performed in 2011 and 2015 to analyze routine practice for myeloma patients outside clinical trials in Germany. We contacted university hospitals, community hospitals, and office-based hematologists in order to enter clinical data from newly diagnosed and relapsed patients into an online platform. Complete datasets were available for 478 (2011) and 515 (2015) patients. While median age at diagnosis increased from 70 to 72 years, patients had fewer concomitant diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
8
2
Order By: Relevance
“…Furthermore, the observed MM treatment patterns are similar to those reported in previous publications of real-world data from Germany. 36,37 These factors, along with the large sample size included, suggest that our HRQoL results should be generalizable to Germany as a whole. Moreover, the similarities between our data and those reported from France 34 and Spain 35 suggest that these results may be more widely generalizable across Europe.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the observed MM treatment patterns are similar to those reported in previous publications of real-world data from Germany. 36,37 These factors, along with the large sample size included, suggest that our HRQoL results should be generalizable to Germany as a whole. Moreover, the similarities between our data and those reported from France 34 and Spain 35 suggest that these results may be more widely generalizable across Europe.…”
Section: Discussionmentioning
confidence: 94%
“…In the current study, patient outcomes with cilta-cel, as observed in CARTITUDE-1, were compared with outcomes from similar patients treated with RWCP, as observed in Therapie Monitor in Germany. Therapie Monitor provides a representative sample of patients from German routine clinical practice and has excellent variable coverage, ensuring reliable comparisons [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. This is further illustrated by the observed median OS and TTNT in Therapie Monitor of 9.89 and 6.21 months, respectively, consistent with outcomes in other sources and geographies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the prevalent target population among the considered therapy regimens was based on the results from a nationwide, multi-institutional survey on treatment of multiple myeloma patients in Germany (TherapyMonitor) [13]. Previous analyses revealed that the database from the TherapyMonitor has a good external validity to the German population regarding the distribution of treated patients with multiple myeloma [14].…”
Section: Patient Populationmentioning
confidence: 99%